PENGUATAN KARAKTER KEBANGSAAN PESERTA DIDIK DI SEKOLAH INDONESIA (SINGAPURA), LTD. - Berliana, Religia Fatihasari; Yuliandari, Erna; ., Triyanto (Prodi PPKn FKIP UNS, 2018)
ABSTRACTThe purposes of this research were to find out (1) The condition of nation insight from the student of Indonesian School (Singapore), Ltd. (2) The strategies of Indonesian School (Singapore), Ltd for strengthening the student?s nation character, (3) The obstacles of strengthening the student?s nation character in Indonesian School (Singapore), Ltd.This research used qualitative research methods with descriptive research as the type of research. The data consisted of: Informant, Observation, and Document. The sampling technique that has been used is purposive sampling, and the data were gathered by in-depth interview, observation, and literature review. The data were analyzed using Miles and Huberman that is consisted four components, such as data collection, data reduction, data display, and conclusionThe results of this research were: (1) The condition of student?s nation insight knew as follow: (a) there were still several students who do not know Indonesian?s nation insight well, because they are seldom living in Indonesia, and their parent do not support them for preserving national identity of Indonesia, (b) Most of the students knew the material theoretically but they could not implement it well. (2) The strategies of Indonesian school (Singapore), Ltd. for strengthening the student?s nation character were implemented on (a) Teaching learning process in class through civic education, art education, history, bahasa, and another major that are suitable for implementing nation character learning such as sociology and economics. (b)Extracurricular activities, such as traditional music, traditional dance, and scout, (c) School cutural activities such as ceremony, activities related with showing art, etc. (3) The obstacles of strengthening student?s nation character were (a) there was low awareness from the student for knowing that the national identity of Indonesia must be preserved by them as the next nation generations, (b) there was a limited teacher for teaching student about nation character exactly through civic education, (c) modernization in globalization era makes the student chose to have western lifestyle. Keywords: Nation Character, Strengthening, Student